Analisis Bentuk Dan Makna Visual pada Film Animasi Pacu Baluluak (Tinjauan Semiotika) - Diana Erwilla Rahmi; Jupriani Jupriani (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This research aimed to describe visual meaning in animation movie Pacu Baluluak. study used qualitative descriptive method. This research problem on visual analysis (colour, gesture, and character), with a little review about Pacu Baluluak animation. In order to analyze the data, the researcher used semiotics review by Roland Barthes to define three meaning levels (denotative, connotative, and myth) on some scenes and visual (colour, gesture, and character) in Pacu Baluluak animation documented by the researcher. From the research result, it can be concluded that Pacu Baluluak animation has a good visual communication strategy in creating character, in a form of gesture, colour, and character so that it illustrates a strong character. The moral value in this animation is arranged well with a simple illustration, so that we can easily follow and understand the storyline.